Nottingham Experience with The Fixed Bearing Infinity Total Ankle Replacement. Issue 4 (22nd October 2020) - Salem-Saqer, Hatem; Raglan, Martin; Dhar, Sunil
Category: Ankle; Ankle Arthritis Introduction/Purpose: Total ankle arthroplasty (TAA) is increasingly used for treatment of end stage arthritis of the ankle; improvements continue to evolve in implant design and instrumentation. We present our experience of the Infinity Total Ankle Arthroplasty (Wright Medical), a fixed bearing 4th generation implant with improved instrumentation Methods: This is a retrospective review of prospectively collected data. From October 2016 to July 2019, we identified 92 (52M/40F) who had the infinity Total Ankle Replacement. This review is of 70 patients with a minimum of 1 year follow up (33M, 37F). The mean age was 67.5 years (33-87); 32 right side and 38 left no bilaterals. The indication for surgery was end stage Osteoarthritis in 52, post traumatic arthritis 12, inflammatory arthritis 4, conversion of fusion to TAR 2. The preoperative deformity was graded according to the COFAS classification. All patients had follow up at 6 weeks, 3, 6 and 12 months and then annually, with MOXFQ questionnaire and weight bearing radiographs. Results: TAA was performed with the use of fluoroscopy. 77% (54/70) had concomitant procedures as listed in Table.5% (4/70) had complications consisting of, 1 DVT, 1 intra operative medial malleolus fracture, 1 EHL tendon laceration and 1 wound break down. There were no deep or superficial infections. Improvement in clinical outcome and PROMS data was noted on follow up. The MOXFQ for Pain improved from 72 pre-op to 25 at 1year (p<0.001). The outcome for Walking improved from 83 pre-op to 30 at one year (p<0.001). Radiological alignment was maintained asymptomatic posterior heterotopic ossification was noted in 23(16%) patients, lucent lines under the tibial implant were noted in 4 ankles and 1 fibula erosion. 2 TAA (3%) needed to be revised due to malpositioning. Conclusion: Our results show significant improvement in patient outcomes, a short recovery time and marked improvement in mobility post operatively with a very low complication rate, we had no deep infection to date. Two implants were revised which we attribute to the learning curve at the start of practice. This implant is fluoroscopically navigated allowing precise implantation with dedicated instrumentation and we feel this attributed to the low complication rate and good results in our short-term study